MARKETING RESEARCH IN THE FIELD OF PUBLIC ADMINISTRATION - Sychenko, Viktor; Kudyrko, Olha (Public Administration and Regional Development, 2024)
The article defines the peculiarities of marketing research in the field of public administration. The purpose of the study is to justify the relevance and expediency of using marketing tools in the field of public administration to increase the effectiveness of the activities of state bodies and the public, in particular, conducting marketing research. In the conditions of reforming the sphere of public administration, one of the key vectors became the use of a client-oriented approach in work, the implementation of which can increase the efficiency of the activities of state bodies. Understanding the needs of citizens and determining satisfaction with services can be considered the key advantages of implementing marketing research into the work of state bodies, which in the future allows for the development of effective state programs; improvement of the process of providing services thanks to the change of formats of interaction with citizens based on understanding their requests; formation of a positive image of state bodies due to the development of effective communication strategies that will contribute to increasing trust in the state, etc. In the course of the study, the key features of marketing research in the field of public administration were grouped and a comparison was made with the commercial sector, which proved the need to use appropriate personalized data collection methods that would reflect the needs of specific population groups. The data collection algorithm was summarized and the analysis of the main elements of the marketing research process for the field of public administration was carried out, in particular, the question of qualitative research methods, which can be used when collecting primary information from respondents, was investigated in detail. In the results of the study, it was determined that the use of marketing research as a tool of interaction with citizens allows to make public services more efficient, personalized and transparent.